The art of being unreasonable lessons in unconventional thinking - Eli Broad, with Swati Pandey (Hoboken, NJ John Wiley & Sons, 2012)
Eli Broad?s embrace of "unreasonable thinking" has helped him build two Fortune 500 companies, amass personal billions, and use his wealth to create a new approach to philanthropy. He has helped to fund scientific research institutes, K-12 education reform, and some of the world?s greatest contemporary art museums. By contrast, "reasonable" people come up with all the reasons something new and different can?t be done, because, after all, no one else has done it that way. This book shares the "unreasonable" principles-from negotiating to risk-taking, from investing to hiring-that have made Eli Broad such a success.
Includes index
Keywords: Broad, Eli